Gli1+-PDL Cells Contribute to Alveolar Bone Homeostasis and Regeneration. (November 2022) - Shalehin, N.; Seki, Y.; Takebe, H.; Fujii, S.; Mizoguchi, T.; Nakamura, H.; Yoshiba, N.; Yoshiba, K.; Iijima, M.; Shimo, T.; Irie, K.; Hosoya, A.
The periodontal ligament (PDL) contains mesenchymal stem cells (MSCs) that can differentiate into osteoblasts, cementoblasts, and fibroblasts. Nevertheless, the distribution and characteristics of these cells remain uncertain. Gli1, an essential hedgehog signaling transcription factor, functions in undifferentiated cells during embryogenesis. Therefore, in the present study, the differentiation ability of Gli1 + cells was examined using Gli1-CreERT2/ROSA26-loxP-stop-loxP-tdTomato (iGli1/Tomato) mice. In 4-wk-old iGli1/Tomato mice, Gli1/Tomato + cells were only slightly detected in the PDL, around endomucin-expressing blood vessels. These cells had proliferated over time, localizing in the PDL as well as on the bone and cementum surfaces at day 28. However, in 8-wk-old iGli1/Tomato mice, Gli1/Tomato + cells were quiescent, as most cells were not immunoreactive for Ki-67. These cells in 8-wk-old mice exhibited high colony-forming unit fibroblast activity and were capable of osteogenic, chondrogenic, and adipogenic differentiation in vitro. In addition, after transplantation of teeth of iGli1/Tomato mice into the hypodermis of wild-type mice, Tomato fluorescence indicating the progeny of Gli1 + cells was detected in the osteoblasts and osteocytes of the regenerated bone. These results demonstrate that Gli1 + cells in the PDL were MSCs and could contribute to the alveolar bone regeneration.